FATTY ACIDS FROM BEEF FEED TO BEEF MEAT - Nesic, Ksenija (Food and Feed Research, 2024)
Beef meat has exceptional nutritional value that distinguishes it from other types of meat and makes it a highly valued food. However, the meat of cattle as well as other ruminants, is characterized by a more complex fatty acid profile compared to the meat of monogastric animals. This complexity is a consequence of the activity of the rumen microflora.In recent decades, changes in animal breeding, feeding practices, and modern slaughtering techniques imparted significant progress in improving beef's nutritional, sensory and market value. Different proportions of concentrated feed and roughages, as well as their types, affect the composition of intramuscular fat. Excluding genetic factors and production practices, nutrition emerges as the main factor influencing the fatty acid profile of beef meat.Today, numerous studies support the nutritional approach to modifying the fatty acid composition of beef meat by using selected feedingstuffs. Therefore, this review aims to collect and systematize data as a guide for implementing such a nutritional strategy in practice, with the health benefits of the final consumers in mind.